Students' Reception of Social Phenomena in Tere Liye's Novels - Fathiyah, Fathiyah; Anshari, Anshari; Juanda, Juanda (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to identify the influence of implicit readers in the novel Bandit-Bandit Berkelas by Tere Liye on students' interpretation of social phenomena, explore how students fill the gaps in the text, and analyze the process of meaning actualization based on Wolfgang Iser's literary reception theory (1978). The method used was a mixed method involving 54 students of Makassar State University of Indonesian Language and Literature department. Data were obtained through closed questionnaires with Likert scale analysis and open questionnaires with thematic analysis. The results showed that the novel had a significant impact in shaping students' interpretations of social phenomena, particularly organized crime and corruption. The implicit reader in the novel encourages students to be more critical of social injustice. Text gaps allow students to actively fill in the narrative gaps through imagination and personal experience, enriching their understanding of the storyline and characters. In addition, the process of meaning actualization takes place continuously after the reading is completed, showing that the novel is not only an entertainment, but also a tool of reflection on complex social structures. This research confirms that literary works can be an effective medium in raising students' social awareness and critical thinking.